The use of estramustine phosphate in the modern management of advanced prostate cancer - Ravery, Vincent; Fizazi, Karim; Oudard, Stephane; Drouet, Ludovic; Eymard, Jean‐Christophe; Culine, Stephane; Gravis, Gwenaelle; Hennequin, Christophe; Zerbib, Marc (BJU international, 2011)
What’s known on the subject? and What does the study add? Estramustine phosphate has anti‐tumour properties and it improves patient outcomes if combined with other chemotherapy agents such as doeetaxel. The efficacy of estramustine phosphate in selected patients and its safety profile, provided used with any low‐molecular‐weight heparin support its use as a second‐line treatment in hormone‐resistant prostate cancer. OBJECTIVES • Estramustine phosphate is a nitrogen mustard derivative of estradiol‐17β‐phosphate and has anti‐tumour properties. • Interest in estramustine has been renewed because of the results of clinical studies showing improved patient outcomes if estramustine is combined with other chemotherapy agents such as docetaxel. PATIENTS AND METHODS • Relevant clinical studies using chemotherapy combinations including estramustine are discussed. • Efficacy and safety outcomes are summarized. RESULTS • Combination therapy with estramustine and docetaxel can increase PSA response rates, improve quality of life and increase median patient survival compared with chemotherapy regimens that do not include estramustine. • Although the overall tolerability of estramustine is favourable, its use can be associated with an increased risk of thromboembolic events. CONCLUSIONS • The identification of suitable patient groups and the effective management of the risk of thromboembolism with the adjunct of low‐molecular‐weight heparins support the use of estramustine as an effective second‐line treatment strategy in hormone‐resistant prostate cancer. • These promising findings warrant further investigation in a randomized clinical trial.